ANALISIS PERLINDUNGAN KOROSI GEARBOX PADDLE WHEEL AERATOR DENGAN PELAPISAN NIKEL MENGGUNAKAN METODE ELEKTROPLATING - Abu Zamani; Priyambodo Nur Ardi Nugroho; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Corrosion of paddle wheel aerator gearboxes is a major factor affecting their performance in shrimp farms. To maintain its performance, protection from corrosion of the gearbox is necessary. This study focuses on the effect of nickel electroplating on corrosion rate. Electroplating is a way of coating metals with electric current. The variations used were electroplating current and time, then analyzed using the weight loss test. The results showed that the thickest coating occurred in the variation of 4A and 30 minutes, about 1.03 mm. The thinnest coating occurred in the 1A and 10 minutes variation, which was 0.10 mm. The lowest corrosion rate is at variation 4A and 30 minutes, which is about 0.1655 mmpy. The highest corrosion rate was in the 1A and 10 min variation, which was about 0.4246 mmpy. The greater the electroplating current and time, the more the service life of the coating increases. The conclusion of this research is that nickel plating by electroplating can reduce the corrosion rate of the aerator gearbox by about 92%, because the corrosion rate of the coated one is lower than the uncoated one.